Valorization of chia (Salvia hispanica) seed cake by means of supercritical fluid extraction - Guindani, Camila; Podestá, Rossana; Block, Jane M.; Rossi, Márcio J.; Mezzomo, Natália; Ferreira, Sandra R.S. (The Journal of supercritical fluids, 2016)
•The re-use of chia seed cake as raw material to obtain bioactive extracts is a novelty.•Chia seed cake extracts presented the same quality that whole chia seeds extracts.•Chia seed cake extracts are rich in ω-3 and ω-6 fatty acids and phenolic compounds.•Biological and nutritional valuation of an agroindustrial waste were achieved.•SFE from chia seed cake is profitable and produces extracts with a competitive price. Chia (Salvia hispanica) seed is a source of natural antioxidants and essential fatty acids. The present study evaluated the oil extraction from chia seed cake, a residue from chia seed oil extraction by cold pressing. Extraction conditions (pressure, temperature, solvent) and its effects in the quality of the extracts were studied. The re-use of an agroindustrial residue (chia seed cake) for obtaining extracts rich in bioactive compounds (high added value), mainly using the supercritical technology, is a novelty. Published studies on this subject have not been found. Supercritical fluid extraction (SFE) was performed at pressures from 150 to 300bar and temperatures of 40–50°C, using CO2 as solvent or CO2 added to ethanol (EtOH) or ethyl acetate (EtOAc) as cosolvents at 2.5–7.5% w/w of the total CO2 mass. Extracts obtained by SFE were compared to extracts obtained by low-pressure techniques (LPE), using hexane, EtOH, and EtOAc as solvents. All extracts were evaluated as antioxidant content (ABTS and DPPH methods), total phenolics content (TPC), fatty acids profile (GC-FID) and in vitro antimicrobial activity analysis. SFE assays using pure CO2 reached yields up to 10.6±0.2% at 300bar and 50°C. SFE with 7.5% of EtOH increased the process yield and TPC of the extract. LPE techniques using EtOH and EtOAc produced extracts with the best TPC values (50±3 and 79±2mg CAE/gextract, respectively) and EC50 values (760±19 and 621±11μg/mL, respectively). GC-FID confirmed the high content of linoleic and α-linolenic acids (∼80% together), and the presence of palmitic, stearic and oleic acids, in minor amounts for all of the extract samples evaluated. It was noted that chia seed cake extracts presented the same quality that whole chia seed extracts, studied by other authors. Extracts obtained by different techniques also showed weak antimicrobial activity against B. cereus. The economic evaluation indicated SFE of chia seed cake is a profitable way to reuse this agroindustrial waste.